The association between glycaemic control and lifestyle habits in adults with Type 2 Diabetes Mellitus attending selected private health care practices in Thabazimbi, Limpopo Province. - Carstens, Maryke (Stellenbosch : Stellenbosch University, 2013)
Thesis (MNutr)--Stellenbosch University, 2013.